Assessing Users Involvement in Analysis and Design Tasks of Electronic Health Information Systems: Experiences, Challenges, and Suggestions to Optimise Involvement - Akello, Christine Kalumera; Bbosa, Francis Fuller; Nabukenya, Josephine (Journal of Health Infomatics in Africa, 2019)
Background: User requirements play a vital role in the development of usable EHIS. For developers to design better quality, relevant and safer EHIS that meet user needs, they are required to actively engage stakeholders especially in the analysis and design tasks of its development life cycle. This is because they provide context appropriate solutions based on their needs. However, in most cases developers ignore health stakeholders’ input especially during these tasks due to varying perspectives and expectations, complexity, high cost, and variability in time to complete the tasks. This has resulted into various challenges including difficulty in capturing and interpreting user requirements in an effective and efficient manner, poorly designed and unusable systems, unsatisfied user needs, and high maintenance costs. This study thus aimed at assessing users’ involvement in the analysis and design tasks when developing EHIS with a view to understand their experiences, challenges, and suggestions to optimise their involvement. Methods: We employed a cross-sectional survey to investigate and describe the level of user involvement and challenges faced in the analysis and design tasks of the EHIS development process. A total of 36 health practitioners from 13 Key health institutions located in Uganda were selected as respondents. Results: The study revealed that majority of the respondents was involved in EHIS development, with a few involved at analysis and design tasks. Increased costs associated with data collection, followed by lack of consensus in clarifying, articulating and defining user requirements were recorded as the biggest challenges faced by users at requirements gathering, analysis and system design tasks. Regards suggestions to optimising users’ involvement in EHIS development tasks, the study reported that users were very much interested in being involved at all tasks of EHIS development, and consultation of users was paramount in order to incorporate all their needs in EHIS. Conclusions: The results from the study demonstrate the value of user involvement at the analysis and design tasks of EHIS development cycle. User involvement offers benefits in form of reduction in costs, improved productivity due to users easily arriving at a common consensus and positive growth in user attitudes. The researchers intend to incorporate suggestions that emerged from this study to conduct long-term evaluations of existing EHIS and investigate how users’ involvement changes over time.